Perancangan Pembelajaran Interaktif Berbasis Multimedia Pada Anak TK Menggunakan Metode Research and Development (R&D) - Fitrian, Muhammad Ghilang; Rangga, Andi Yusika; Hasiholan, Jundro Daud (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Early childhood reading ability is an essential foundation for subsequent academic development. The main problem at Mekar Sari Kindergarten is the low reading interest of children, characterized by frequent boredom and easily distracted attention during conventional learning. This study aims to develop an interactive multimedia learning system based on the VAK (Visual, Auditory, Kinesthetic) approach to create a more engaging and meaningful learning experience. The method used is Research and Development (R&D) with a prototyping approach through participatory observation and in-depth interviews with teachers. The contribution of this research lies in the design of an interface that organically integrates multimodal stimuli according to early childhood learning characteristics. The results show that the developed prototype successfully created positive responses where children appeared enthusiastic and actively engaged throughout the learning process. Detailed observations revealed significant improvements in children's attention span and spontaneous participation in learning activities. Feedback from teachers highlighted the ease of integrating this media into the daily curriculum and its effectiveness in maintaining children's engagement. The study concludes with a multimedia system prototype that has been pedagogically proven capable of creating an immersive and enjoyable learning environment for early childhood.